Teaching English to Students with Dysarthria: A Case Study of Show-Listen-Retell Games - Putra, M. Ferdiansyah; Yusra, Kamaluddin (Journal of English Education Forum (JEEF), 2025)
This research uses a case study design to explore how Show-Listen-Retell Games (SLR) affect students with dysarthria learning motivation and speaking skills at Kuta Village, Central Lombok Regency. The SLR method is used to increase students' learning motivation and speaking skills on the aspects are fluency, pronunciation and comprehension, the following aspects that focuses on SLR games show the potential that SLR can also increase speaking skills for normal students. Data from pre-tests and post-tests reveal a transition in motivation categories from a predominance of good pre-test scores to a more evenly distributed post-test outcome of excellent and good categories. The results of this study show two things. First is Hypothesis 1 which state H1 SLR are no significant effect on learning motivation of students with dysarthria is rejected because N = 7, W-count = 7 is smaller than W-table = 19. While the second result is Hypothesis 2 which state H2 SLR are no significant effect on speaking skills of students with dysarthria is rejected because N = 7, W-count = 6 is smaller than W-table = 22. This shows that SLR is successful in improving learning motivation and speaking skills of students with dysarthria. Thus, the research advocates for the implementation of SLR and similar interactive methods in teaching English to students with dysarthria, emphasizing the need for larger sample sizes in future studies to validate findings and expand on effective teaching strategies.